2016
DOI: 10.7717/peerj.1539
|View full text |Cite
|
Sign up to set email alerts
|

IsAcropora palmatarecovering? a case study in Los Roques National Park, Venezuela

Abstract: Eight years ago (2007), the distribution and status of Acropora palmata was quantified throughout Los Roques archipelago in Venezuela. The aim was to produce a baseline study for this species which combined population genetics with demographic data. The results highlighted that A. palmata had the potential to recover in at least 6 out of 10 sites surveyed. Recovery potential was assumed to be high at sites with a relatively high abundance of the coral, low disease prevalence, high genetic diversity, and high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 73 publications
(86 reference statements)
0
22
0
2
Order By: Relevance
“…The area has also been found to be vulnerable to changes in regional oceanographic processes, in particular changes in wind-induced upwelling (Villamizar & Cervigón 2017). Cróquer et al (2016) present evidence that the coral Acropora palmata has lost almost 50% of its original distribution in Los Roques in recent decades. While this level of loss is much lower than most other areas of the Caribbean, it does highlight the continued vulnerability of this species to global threats such as ocean warming.…”
Section: Marine Biodiversitymentioning
confidence: 77%
See 1 more Smart Citation
“…The area has also been found to be vulnerable to changes in regional oceanographic processes, in particular changes in wind-induced upwelling (Villamizar & Cervigón 2017). Cróquer et al (2016) present evidence that the coral Acropora palmata has lost almost 50% of its original distribution in Los Roques in recent decades. While this level of loss is much lower than most other areas of the Caribbean, it does highlight the continued vulnerability of this species to global threats such as ocean warming.…”
Section: Marine Biodiversitymentioning
confidence: 77%
“…While this level of loss is much lower than most other areas of the Caribbean, it does highlight the continued vulnerability of this species to global threats such as ocean warming. Notwithstanding important outbreaks of white band disease among the acroporid corals of Los Roques (Cróquer et al 2005), the park protects one of the few areas of the Caribbean that has retained relatively high densities of Acropora reefs (Zubillaga et al 2005, Cróquer et al 2016) since the mid-1980 when the species declined precipitously throughout the Caribbean. Zubillaga et al (2008) found important signs of population recovery for the species three decades after the Caribbean-wide mass mortality took place.…”
Section: Marine Biodiversitymentioning
confidence: 99%
“…palmata and staghorn corals A . cervicornis historically dominated reefs throughout the Caribbean Sea [ 71 ], but have declined drastically due to the compounding influences of anthropogenic and natural disturbances [ 72 , 73 ], including hurricanes Emily and Wilma which both hit the Yucatan Peninsula in 2005 [ 48 , 49 ]. The relationships examined here between the remaining acroporid percent cover and snorkeling level disappeared when the outer bay (reef crest) sites were removed, indicating their percent cover may be driven more by outer-inner bay physical gradients than snorkeler pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat characterization at each site was assessed qualitatively according to the habitat type, habitat condition and geomorphological unit. Habitat type was based on the main substrate and dominance of benthic species following Croquer et al (2016) and Bernal-Sotelo et al (2019). This rapid characterization is suitable for rough descriptions of the coral benthic communities at spatial scales above 50 m (Hill and Wilkinson, 2004) as in this study.…”
Section: Habitat Characterizationmentioning
confidence: 99%